Kansans Can: Redesigning Education in Kansas - Randy Watson (Educational Considerations, 2020)
In fall 2014, the Kansas State Board of Education charged me with gathering information from Kansans as to what they wanted in their school system. After months of studying the research conducted from listening tours and matching that data to current educational research, the State Board of Education launched a new vision for education in October 2015. This vision had clear metrics for success – Lead the World. Those metrics were all focused on a single point of obtainment – the Success of Each Student. The vision was clear, difficult to achieve, compelling and viewed attainable by 2026. In fall 2017, the State Board launched the first school to redesign around this research and principles, and soon the original seven school districts were working to transform education. Over the next three years, that initial cohort was followed by additional districts. The State Board desires to have all school districts involved in redesign by 2026. Today more than 67 school districts and 170 schools have voluntarily embarked in the redesign process since 2017.
Keywords: Kansas; redesign; pandemic